2012
DOI: 10.1016/j.gloplacha.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Post-disturbance vegetation dynamics during the Late Pleistocene and the Holocene: An example from NW Iberia

Abstract: 24There is a wealth of studies dealing with the reconstruction of past environmental changes and their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 51 publications
1
48
0
4
Order By: Relevance
“…Principal components analysis (PCA) was also performed on the transposed data matrices of the regional and local types and NPP. This type of analysis enables an intuitive interpretation of pollen data from an ecological point of view summarizing the pollen composition of the samples based on co-variation (López-Merino et al, 2012). The pollen and NPP data were log-transformed and standardized (z-scores) before analysis, as suggested for compositional data (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal components analysis (PCA) was also performed on the transposed data matrices of the regional and local types and NPP. This type of analysis enables an intuitive interpretation of pollen data from an ecological point of view summarizing the pollen composition of the samples based on co-variation (López-Merino et al, 2012). The pollen and NPP data were log-transformed and standardized (z-scores) before analysis, as suggested for compositional data (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Taxa included in the TLP are considered to be indicators of the regional vegetation, while hydro-hygrophytes and NPP are considered to mainly provide a local signal. The NPP can be safely considered as local indicators as their dispersal is limited, however the case of the hydro-hygrophyte taxa is more complex, as they could also be part of the regional communities (López-Merino et al, 2012), as for example the Cyperaceae. Pau de Fruta is a valley mire (in an upper catchment position) and variations in the depth of the water table could be responsible for differences in the spatial distribution of local plant communities.…”
Section: Palynological Studymentioning
confidence: 99%
“…The period with low fire activity could be due to better control of fire by humans but more probably to cooler and more humid climate during the Little Ice Age in Spain (MartinPuertas et al, 2008;Morellon et al, 2011). Other relatively close sites show maximum fire activity for the last 2500-3000 years (Allen et al, 1996;Franco-Mugica et al, 2005;Lopez-Merino et al, 2012), in marked contrast with Ayoo record.…”
Section: Human Impact On the Vegetation Of The Northwestern Corner Ofmentioning
confidence: 99%
“…Numerous studies (24% of direct definitions) mention both forms of resilience, represented by differences between sites or by a change in the type of resilience through time (e.g. Bhagwat et al 2012, Lopez-Merino et al 2012, Macken and Reed 2014, Kowlalewski et al 2015, Ryan et al 2016, Swindles et al 2016. Coastal geomorphology "This research leads us to reflect on the concept of "coastal resilience" which, we conclude, means little without a clearly defined spatial and temporal framework... We therefore envisage multiple scales of "resilience" operating simultaneously across the complex, responding to different forcing agents with particular magnitudes and frequencies… "Coastal resilience" describes the self-organising ability of a coast to respond in a sustainable manner to morphological, biological and/or socio-economic pressures" (Long et al 2006: 309-310) Direct: ecological resilience (tolerance or reorganisation)…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only a minority of papers in this review identified or hypothesised a response model (e.g. Woodroffe 2007, Eppinga et al 2009, Gillson & Ekblom 2009, Sayer et al 2010, McLauchlan et al 2014, Lopez-Merino et al 2012. Calls for more explicit definition of response models have also been made recently in the fields of ecology and socio-ecology (e.g.…”
Section: Defining Resiliencementioning
confidence: 99%